Bruton’s Tyrosine Kinase (BTK) Inhibitors and Autoimmune Diseases: Making Sense of BTK Inhibitor Specificity Profiles and Recent Clinical Trial Successes and Failures - Ringheim, Garth E.; Wampole, Matthew; Oberoi, Kinsi (Frontiers in Immunology, 2021)
Clinical development of BTK kinase inhibitors for treating autoimmune diseases has lagged behind development of these drugs for treating cancers, due in part from concerns over the lack of selectivity and associated toxicity profiles of first generation drug candidates when used in the long term treatment of immune mediated diseases. Second generation BTK inhibitors have made great strides in limiting off-target activities for distantly related kinases, though they have had variable success at limiting cross-reactivity within the more closely related TEC family of kinases. We investigated the BTK specificity and toxicity profiles, drug properties, disease associated signaling pathways, clinical indications, and trial successes and failures for the 13 BTK inhibitor drug candidates tested in phase 2 or higher clinical trials representing 7 autoimmune and 2 inflammatory immune-mediated diseases. We focused on rheumatoid arthritis (RA), multiple sclerosis (MS), and systemic lupus erythematosus (SLE) where the majority of BTK nonclinical and clinical studies have been reported, with additional information for pemphigus vulgaris (PV), Sjogren’s disease (SJ), chronic spontaneous urticaria (CSU), graft versus host disease (GVHD), and asthma included where available. While improved BTK selectivity versus kinases outside the TEC family improved clinical toxicity profiles, less profile distinction was evident within the TEC family. Analysis of genetic associations of RA, MS, and SLE biomarkers with TEC family members revealed that BTK and TEC family members may not be drivers of disease. They are, however, mediators of signaling pathways associated with the pathophysiology of autoimmune diseases. BTK in particular may be associated with B cell and myeloid differentiation as well as autoantibody development implicated in immune mediated diseases. Successes in the clinic for treating RA, MS, PV, ITP, and GVHD, but not for SLE and SJ support the concept that BTK plays an important role in mediating pathogenic processes amenable to therapeutic intervention, depending on the disease. Based on the data collected in this study, we propose that current compound characteristics of BTK inhibitor drug candidates for the treatment of autoimmune diseases have achieved the selectivity, safety, and coverage requirements necessary to deliver therapeutic benefit.